Transforming Europe : Europeanization and domestic change - Cowles, Maria Green, 1961-; Caporaso, James A., 1941-; Risse-Kappen, Thomas (Cornell studies in political economy., 2001)
Does the European Union change the domestic politics and institutions of its member states? Many studies of EU decisionmaking in Brussels pay little attention to the potential domestic impact of European integration. Transforming Europe traces the effects of Europeanization on the EU member states. The various chapters, based on cutting-edge research, examine the impact of the EU on national court systems, territorial politics, societal networks, public discourse, identity, and citizenship norms. The European Union, the authors find, does indeed make a difference-even in Germany, France, and the United Kingdom. In many cases EU rules and regulations incompatible with domestic institutions have created pressure for national governments to adapt. This volume examines the conditions under which this "adaptational pressure" has led to institutional change in the member states